2016
DOI: 10.1021/jacs.6b07530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of H-Bonding on Order Amplification in the Growth of a Supramolecular Polymer in Water

Abstract: While a great deal of knowledge on the roles of hydrogen bonding and hydrophobicity in proteins have resulted in the creation of rationally designed and functional peptidic structures, the roles of these forces on purely synthetic supramolecular architectures in water have proven difficult to ascertain. Focusing on a 1,3,5-benzenetricarboxamide (BTA) based supramolecular polymer, we have designed a molecular modeling strategy to dissect the energetic contributions involved in the self-assembly (electrostatic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
158
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(180 citation statements)
references
References 44 publications
22
158
0
Order By: Relevance
“…3a: GC monomer ( 1 )) 25, 30, 31 . Our simulations demonstrated that these stacks are not perfect in water, where fibre folding due to hydrophobic effects produces multiple defects/breakages along the supramolecular polymers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3a: GC monomer ( 1 )) 25, 30, 31 . Our simulations demonstrated that these stacks are not perfect in water, where fibre folding due to hydrophobic effects produces multiple defects/breakages along the supramolecular polymers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13 Besides their use as enantioselective receptors for carbohy-the chirality of the arrangement of the linkers, but also that of the south unit, in particular that of a benzene-1,3,5tricarboxamide (BTA) moiety ubiquitous in supramolecular chemistry. [19][20][21][22][23][24][25][26][27] Herein, we report the synthesis of the new hemicryptophane cage 1. The resolution of the racemic mixture was performed by chiral high-performance liquid chromatography (HPLC), and the assignment of the absolute configuration of the two enantiomers was achieved from electronic circular dichroism (ECD) spectra.…”
Section: Introductionmentioning
confidence: 99%
“…For details of the method, the reader is referred to the Supporting Information. [17,29,31,32] Higher g(c) peaks (relative probability for finding cores at stacking distance c = 3.4 from the neighbors) indicate higher persistence/regularity of the stacking. [17,29,31,32] Higher g(c) peaks (relative probability for finding cores at stacking distance c = 3.4 from the neighbors) indicate higher persistence/regularity of the stacking.…”
mentioning
confidence: 99%
“…[17,29,31,32] Higher g(c) peaks (relative probability for finding cores at stacking distance c = 3.4 from the neighbors) indicate higher persistence/regularity of the stacking. [29,31] Ah igher persistence/order (ca. [29,31] Ah igher persistence/order (ca.…”
mentioning
confidence: 99%